2021
DOI: 10.29333/ejecs/975
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Public Trust in Government During the COVID-19 Pandemic in Indonesia: Mediation of Perceived Religious Values

Abstract: Drawing from social cognitive theory, the current study investigated the direct and indirect relationship of public interaction with government officials on SNS (Social Network Sites), perceived government response on COVID-19, and perceived e-governance effectiveness with the overall public trust in government via an underlying mechanism of the perceived religious value. Using a quantitative field survey at local administration levels, the primary data of 478 individuals were collected from two cities in Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Accountability represents the transparent and responsible nature of individuals and institutions in fulfilling their duties to facilitate the public (Hayati & Aviana, 2021). The current study results align with previous studies conducted in the public administration context and examine the impact of government institutions' accountability on citizens' satisfaction and trust (Hartanto et al, 2021a;Islm et al, 2021;Mansoor, 2021). The accountability of the police reflects their vigilance in informing citizens about their actions and working patterns, ensuring the safety and security of the public, and communicating the same with the citizens (Ojedokun et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Accountability represents the transparent and responsible nature of individuals and institutions in fulfilling their duties to facilitate the public (Hayati & Aviana, 2021). The current study results align with previous studies conducted in the public administration context and examine the impact of government institutions' accountability on citizens' satisfaction and trust (Hartanto et al, 2021a;Islm et al, 2021;Mansoor, 2021). The accountability of the police reflects their vigilance in informing citizens about their actions and working patterns, ensuring the safety and security of the public, and communicating the same with the citizens (Ojedokun et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Simultaneously, accountability presents the fairness and responsiveness of the public institutions towards the citizens for important decisions and actions directly or indirectly linked with the general public (Mansoor, 2021). Research also indicates that when the institutions are accountable to the masses, serve and perform their duties transparently, and consider themselves responsible; they are considered trustworthy (Hartanto, Agussani, & Dalle, 2021a). Regardless of the literature that presents the significance of accountability in building trust among citizens for governments in developed and developing nations, there is a scarcity of literature examining the impact of police accountability in building and enhancing trust among the citizens.…”
mentioning
confidence: 99%
“…These results can be related to the previous studies, highlighting the significance of communication in bridging the gap between government officials and citizens (Dan & Arendt, 2021;Mukarom, 2022). Several studies postulated the important role of e-governance practices in terms of timely communication via digital media to the masses in developing trust among the public (Hartanto et al, 2021a;Khanra & Joseph, 2019;Mansoor, 2021). Whereas the current study has explicitly considered the politicians' communication on various platforms to communicate their point of view and efforts to the public to show them that they are working in the public's best interest, resulting in a higher level of political satisfaction and political trust among the citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Citizens' political trust means they believe in their elected governments' transparency, responsiveness, and accountability (Hartanto et al, 2021a;Mansoor, 2021). Researchers have shown that citizens' trust in the government highly depends upon their perceptions of the elected officials (Han et al, 2021;Hartanto et al, 2021b).…”
Section: Political Communication Political Efficacy Political Ideolog...mentioning
confidence: 99%
“…In addition, the "ß-coefficient, t-value, and p-value" was calculated to determine the significance of the proposed associations. The "Coefficient of Determination (R2)" was assessed to check the theoretical framework fitness (Hair et al, 2010;Hartanto et al, 2021). The R 2 results showed a 50.5%, 47.5%, and 53.7% variance in children's semantic memory, observed activities, and evaluated skills and qualities simultaneously based on the pedagogical documentation and learning environment.…”
Section: Assessment Of the Structural Modelmentioning
confidence: 99%